2020
DOI: 10.1016/j.parepi.2020.e00167
|View full text |Cite
|
Sign up to set email alerts
|

Trends and associated characteristics for Chagas disease among women of reproductive age in the United States, 2002 to 2017

Abstract: Background American trypanosomiasis, commonly referred to as Chagas disease, is caused by a single cell protozoan known as Trypanosoma cruzi ( T. cruzi ). Although those affected are mainly in Latin America, Chagas has been detected in the United States (US), Canada and in many European countries due to migration. Few studies have explored the epidemiology of Chagas within the US or changes in disease burden over the past decade. The objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Estimates suggest that the majority of T. cruzi-infected individuals in the US are immigrants from other Chagasendemic regions of Latin America [11]. As Latin American migration to the US has increased over the past two decades, it is suggested that so have the number of imported Chagas disease cases, especially in southern states [12, 13, 14•].…”
Section: Dynamics Of Epidemiology and Distribution Of Chagas Disease ...mentioning
confidence: 99%
“…Estimates suggest that the majority of T. cruzi-infected individuals in the US are immigrants from other Chagasendemic regions of Latin America [11]. As Latin American migration to the US has increased over the past two decades, it is suggested that so have the number of imported Chagas disease cases, especially in southern states [12, 13, 14•].…”
Section: Dynamics Of Epidemiology and Distribution Of Chagas Disease ...mentioning
confidence: 99%
“…Segundo o boletim epidemiológico do Ministério da saúde (2020), no período de 2007 a 2016, a doença de Chagas acometeu cerca de 850 pessoas com idade média de 33 anos, tendo maior prevalência de casos notificados em os indivíduos do sexo masculino (54,40%). Em relação ao número de casos entre mulheres, a faixa de idade reprodutiva gera maior preocupações devido a possibilidade de transmissão congênita (Ikedionwu et al, 2020).…”
Section: Introductionunclassified